(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
A theatrical style of extreme intimacy is presented, based on small boxes with scenes called "dramatic capsules" or "theatrical capsules". Its conception is developed, from the pataphysical ideas of Alfred Jarry, the galumphing of Miller and the elementary principles of contemporary object theater. The main characteristics of the dramatic capsules are analyzed, their first presentations are reviewed and finally some ideas of their future implementation are given.